PTU-120 A review of patients in a single centre with ileal pouch-anal anastomosis for ulcerative colitis and an assessment of those patients who require on going medical therapy. (28th May 2012) - Allen, N; Garforth, E; Heath, R; Rooney, P
Abstract : Introduction: Restorative proctocolectomy with ileal pouch-anal anastomosis (IPAA) is the surgical therapy of choice for patients with chronic ulcerative colitis. However IPPA is frequently accompanied by early and late complications. A proportion of patients require ongoing medical management which this study assesses. Methods: A prospectively collected hospital database of patients who were followed up after IPAA at a single centre was retrospectively reviewed. A review of all case notes was carried out to assess surgical intervention prior to IPAA. All post operative complications were recorded and an assessment was made of those patients recommenced on medical therapy. Results: 102 patients' case notes were reviewed, (60 male: 42 female mean age 42 years SD of ±12.01). The follow-up is ongoing and is currently between 2 and 193 months. The complications included anastomotic leak (n=4), incisional hernia (n=7), pouchitis (n=36), stenosis (n=15), pre pouch stricture (n=1), ileitis (n=2), enterocutaneous fistula (n=2), perianal fistula (n=6), pouch vaginal fistula (n=5), pouch ulceration (n=8). All patients prior to surgery had a histological diagnosis of ulcerative colitis, 4 patients were reclassified as having Crohn's or indeterminate colitis at further follow-up. There were 13 (12.7%) patients whom were recommenced on medical therapy, including sulphasalazine, budesonide, azathioprine, 6-mercaptopurine and infliximab. Patients who were on antibiotics were not included in these numbers. All patients who were reclassified as having Crohn's were recommenced on medical therapy and seen in a joint gastro/surgical clinic. Conclusion: Long term anastomotic problems are common after IPPA. Most pouch patients do not require additional medical treatment other than antibiotics but 13% need continued complex medical therapy under the care of gastroenterologists and surgeons. Use of steroids is low. Diagnostic problems remain an issue. Competing interests: None declared.